Endocentric Phrases in Mesut Kurtis' album Tabassam (2004): Tagmemeik Kenneth Lee Pike - Arina Haque; Rusda Fauziah Azzadi; Iffat Maimunah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The purpose of this research is to describe the form of endocentric phrases in Mesut Kurtis' Tabassam album and to describe its construction based on Kenneth Lee Pike's tagmemic units. This research is qualitative descriptive research, with the data source of the song lyrics in Mesut Kurtis' Tabassam album. The data collection technique uses the reading-note technique. Data validation techniques by increasing persistence, triangulation, and discussion. Data analysis techniques by collecting data, processing data, reading the entire data, grouping data, and describing the data. The results of this study reveal that the song lyrics on the Tabassam Album by Mesut Kurtis, which consists of 13 songs, contain endocentric phrases with three types, namely: (1) attributive endocentric phrases with a total of three phrases; (2) a three-phase coordinative endocentric phrase; and (3) a positive endocentric phrase with a single phrase. The three types of phrases have various structures.الغرض من هذا البحث هو وصف شكل العبارات المركزية في ألبوم مسعود كورتيس تباسم ووصف بنائه بناءً على وحدات تغميميك لكينيث لي بايك. هذا البحث هو بحث وصفي نوعي ، بمصدر بيانات كلمات الأغنية في ألبوم مسعود كرتيس تبسم. تستخدم تقنية جمع البيانات أسلوب قراءة الملاحظات. تقنيات التحقق من صحة البيانات عن طريق زيادة المثابرة والتثليث والمناقشة. تقنيات تحليل البيانات من خلال جمع البيانات ومعالجة البيانات وقراءة البيانات بالكامل وتجميع البيانات ووصف البيانات. وتكشف نتائج هذه الدراسة أن كلمات الأغنية في ألبوم تباسم لمسعود كيرتس ، والمكونة من 13 أغنية ، تحتوي على جمل مركزية ذات ثلاثة أنواع ، وهي: (1) جمل منسوبة داخلية بمجموع ثلاث جمل. (2) عبارة مركزية داخلية تنسيقية ثلاثية المراحل ؛ و (3) عبارة إيجابية متمحورة حول الذات مع عبارة واحدة. الأنواع الثلاثة من العبارات لها هياكل مختلفة.